Kebiri Kimiawi Dalam Perspektif Hukum Islam - Wahyudi, Wahyudi (Istinbath : Jurnal Hukum, 2019)
Abstract Increased sexual violence against children can jeopardize the survival of a nation, child development will be disrupted if experienced sexual violence. The government has an important role to protect children as assets of the next generation one of the forms of protection as a deterrent effect for perpetrators of sexual violence against children by giving a weighting penalty with chemical castration punishment. Even though the Indonesian State is not an Islamic State, the majority of the population is Muslim, so that in every decision of the laws and regulations, especially those related to chemical castration punishment are in connecting with Islamic law. This study uses a normative juridical method, which is assessed by the the statute approach meaning that a problem will be seen from the legal aspect by examining the laws and regulations, in addition to that also by the method of library research. The results of this study concluded that the chemical castration penalty contained in Articles 81 and 82 of Constitutions Number 17 Year 2016 Regarding the Establishment of Government Regulation in Lieu of Law Number 1 Year 2016 Regarding the Second Amendment of Law Number 23 Year 23 concerning Child Protection. Chemical castration according to Islamic Law is unlawful based on the Qur'an and Sunnah which is the highest legal source of Islamic law. In various books of the hadith Bukhari and Muslim explained that Rasulallah SAW forbade castration to humans.